Geo-servicios electrónicos de la administración pública autonómica y local en Aragón (España) - Escolano Utrilla, Severino; Salvador Oliván, José Antonio (Geographicalia, 2014)
We examine, first, the main problems in operation of basic educationand health-care services in rural areas to provide the local population efficiently; and second, the local population’s suggestions of how to solve these difficulties, improve the provision and quality of the services, and integrate their equipment into local development processes. Having based the investigation on a qualitative methodology (interviews) and focusing on the local key actors, the indicated problems and solutions are characterised by flexibility and multifunctionality. However, not all offered solutions can be applied simultaneously, since some of them require time to be developed.
Keywords: Educational services; health services; rural space; LEADER; Valencia.